2021
DOI: 10.1021/acs.inorgchem.1c01957
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Magnetism, and Thermal Stability of La2NiO2.5F3: A Ruddlesden–Popper Oxyfluoride Crystallizing in Space Group P42/nnm

Abstract: We report on the new Ruddlesden–Popper (RP) oxyfluoride La2NiO2.5F3 containing an unprecedented high amount of fluorine and Ni2+. This oxyfluoride was prepared by topochemical low-temperature fluorination of La2NiO4, which was obtained by a soft chemistry synthesis, with poly­(vinylidene difluoride) (PVDF) as fluorinating agent. La2NiO2.5F3 is the first n = 1 RP compound crystallizing in the tetragonal space group P42/nnm (a = 5.7297(6) Å and c = 13.0106(2) Å). The crystal structure shows a unique tilting sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…This can be explained by the larger ionic radii 42 of Ba 2+ than La 3+ and In 3+ , which increase the in-plane space requirements, resulting in a significant increase of the long crystallographic axis (+0.62 Å for LaBaInO 4 → LaBaInO 3 F 2 as compared to +0.17 Å for La 2 NiO 4 → La 2 NiO 3 F 2 45 ). Similar behavior was also observed recently by Jacobs et al 47 for the La 2 NiO 4 → La 2 NiO 3 F 2 → La2NiO 2.5 F 3 series, where the Ni−F ap distance decreases with increasing interstitial anion occupation.…”
Section: Structural Analysis Of Labaino 4 and Itssupporting
confidence: 90%
See 1 more Smart Citation
“…This can be explained by the larger ionic radii 42 of Ba 2+ than La 3+ and In 3+ , which increase the in-plane space requirements, resulting in a significant increase of the long crystallographic axis (+0.62 Å for LaBaInO 4 → LaBaInO 3 F 2 as compared to +0.17 Å for La 2 NiO 4 → La 2 NiO 3 F 2 45 ). Similar behavior was also observed recently by Jacobs et al 47 for the La 2 NiO 4 → La 2 NiO 3 F 2 → La2NiO 2.5 F 3 series, where the Ni−F ap distance decreases with increasing interstitial anion occupation.…”
Section: Structural Analysis Of Labaino 4 and Itssupporting
confidence: 90%
“…LaBaInO 4 appears dark brown to the eye, whereas LaBaInO 3 F 2 powders possess a dull hue white represented in the Supporting Information (see SI, insets of Figure S9). In a recent study, Jacobs et al 47 reported on the oxyfluoride system prepared by topochemical low-temperature fluorination of La 2 NiO 4 with PVDF to La 2 NiO 3 F 2 and La 2 NiO 2.5 F 3 , which show a strong bandgap increase compared to La 2 NiO 4 (3.2, 3.4 vs 1.3 eV, respectively).…”
Section: Optical Propertiesmentioning
confidence: 99%
“…These results demonstrate that the B-oxidation state is not significantly changed by the fluorination, confirming the non-oxidative nature of the fluorination process with PVDF as fluorine source. The same was previously found for La 2 NiO 3 F 2 and La 2 NiO 2.5 F 3 . IR-spectra of the reaction products were recorded to check for any residual PVDF or other carbon-containing compounds.…”
Section: Resultsmentioning
confidence: 63%
“…The same was previously found for La 2 NiO 3 F 2 22 and La 2 NiO 2.5 F 3 . 26 IR-spectra of the reaction products were recorded to check for any residual PVDF or other carbon-containing compounds. The corresponding spectra are shown in Figure S1, and the absence of impurities indicates a complete reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The use of more reactive precursor oxides obtained by the citrate-based route at lower calcination temperatures has been successful in the synthesis of La 2 CuO 3 F 2 as well as La 2 NiO 2.5 F 3 . Therefore, this approach was used for the precursor oxides in this work.…”
Section: Resultsmentioning
confidence: 99%